Neutrality in public service interpreting - Zuzana Balounová (Verba Hispanica, 2021)
Most of the interpreting in the world today is done by public service interpreters. However, there has been a great deal of confusion regarding public service interpreting (PSI), specifically the role of the interpreter and neutrality in PSI. While codes of ethics assert that public service interpreters must act neutrally and impartially, users of PSI tend to view the interpreter as their advocate, making it difficult for the interpreter to maintain neutrality. In fact, as previous studies have shown, maintaining neutrality is one of the biggest challenges public service interpreters face. This article provides a review of the existing literature on the role of public service interpreters, ranging from early studies (e.g., Roberts, 1997; Wadensjö, 1998; Pöchhacker, 2000) via more recent work (e.g., Hale, 2008; Kalina, 2015; Valero Garcés, 2015) to the latest studies on the issue (e.g., Balogh & Salaets, 2019; Şener & Kincal, 2019; Runcieman, 2020). Using practical examples, the article analyses some of the existing codes of ethics and professional guidelines, which, as several authors suggest, are insufficient and should be reassessed. Throughout the paper, differences in different PSI settings (e.g., healthcare centres, schools, social services offices) are addressed.